Sustainability marketing at the farmers' market: An ethnographic analysis of ambiguous communication. (12th October 2018) - Garner, Benjamin
Abstract: Farmers' markets have grown rapidly in recent decades. One explanation for this growth relates to consumers' view that farmers' market products are more sustainable. While many have analyzed customer preferences at farmers' markets, few have examined farmers' message strategies in this space. Little has been done to analyze the ways farmers use sustainability as a marketing approach. This ethnographic research is based on 100 hr of observation and in‐depth interviews with 36 participants and analyzes the ways farmers position their products as sustainable to customers. The findings indicate that sustainability is not a primary topic of conversation during customerfarmer interaction. However, related concepts such as environment, local, organic, and chemical serve as the proxies for sustainability, even though these messages are presented ambiguously.